The Influence of Learning Method toward Learning Outcome Kalkulus Diferensial of Students’ Mathematic Education - Siti Qomariyah; Ummi Rosyidah (Bulletin of Science Education, 2022)
This article aimed to find out the effect of learning methods on differential calculus learning outcomes and knowing how much influence learning methods on differential calculus learning outcomes of Mathematics Education students at Universitas Nahdlatul Ulama Lampung. This research was quantitative research with survey method. The research sample was 34 students. The collecting data used close questionnaire to measure the variables of learning methods and documentation to determine the learning outcomes of the differential calculus course. The test of the learning method questionnaire obtained 43 valid statement items with a reliability of 0.90. The result shows that there was an influence between the way of learning on the learning outcomes of Differential Calculus in Mathematics Education students at Nahdlatul Ulama University Lampung. Analysis of the data used is simple regression, with the results obtained by the correlation tcount of 3.148, ttable of 1.694 at a significance level of 5%, and R2 of 0.236, then the results obtained tcount 3.146 > ttable 1.694. Hence, it can be concluded that there was an effect of learning methods on the learning outcomes of Differential Calculus in Mathematics Education Students at Nahdlatul Ulama University Lampung. Keywords: Learning Outcome, Kalkulus Diferensial, Learning Method